Speech Anxiety in the Communication Classroom During the COVID-19 Pandemic: Supporting Student Success - Prentiss, Suzy (Frontiers in Communication, 2021)
A wealth of literature clearly supports the presence of speech anxiety in the communication classroom, especially in those classes with a focus on public speaking and/or presentations. Over the years, much work has been done on intentional approaches to empowering students to effectively manage their speech anxiety in face-to-face, hybrid, and online communication courses. These research-based findings have led to best practices and strong pedagogical approaches that create a supportive classroom culture and foster engaged learning. Then COVID-19 appeared, and things changed. In an effort to keep campuses safe and save the spring semester, everyone jumped online. Many instructors and students were experiencing online education for the first time and, understandably, anxiety exploded. Between the uncertainty of a global pandemic, the unchartered territory of a midterm pivot to fully online education, and the unknown effects of the situation on our educational system, our stress levels grew. Public speaking and presentations took on new meaning with Zoom sessions and webcams and our speech anxiety, undoubtedly, grew, as well. Reflecting upon the scholarship of the past with an appreciation of our present situation and looking toward the future, we will curate a list of best practices to prepare students to effectively manage their speech anxiety with agency, ability, and confidence.